Engineering computations, volume 32, issue 4 : advances in computational particle based methods. (Engineering Computations: Volume 32, Issue 4., 2015)
Computational particle based methods provide unique and powerful numerical tools for modelling systems exhibiting discrete and/or discontinuous behaviour, such as granular materials. Such systems are highly heterogeneous, typically composed of voids and particles with different sizes and shapes. Geological matter, soil and clay, soil-rock mixture in nature, geo-structure, concrete, etc. are some practical examples. Significant progress has been made in the development of particle based computational methods for granular materials in China over the last decade. This special issue contains 14 se.